2020
DOI: 10.4314/evj.v24i2.9
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral testicular degeneration in dogs: Effects on spermatozoal characteristics, testis and cauda epididymis

Abstract: Testicular degeneration is an important cause of poor fertility in dogs, but there is little knowledge on its effects on spermatozoa in affected dogs. The study investigated the specific effects of unilateral testicular degeneration (UTD) on spermatozoal characteristics in the testis and epididymis. Ten sexually mature Nigerian indigenous breed of dogs, comprising 5 normal dogs and 5 dogs with UTD were used for the study. The testis and epididymis were removed via orchidectomy for morphological and histopathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Other researchers have reported similar results in impaired spermatogenesis and a decrease in sperm parameters in dogs treated with Sodium chloride solution (Canpolat et al, 2016). The epididymal sperm concentration reflected a decrease in spermatogenesis in the testes (Oguejiofor et al, 2020). In the treatment groups, vacuolation of ductus epithelium of epididymis was detected.…”
Section: Discussionmentioning
confidence: 95%
“…Other researchers have reported similar results in impaired spermatogenesis and a decrease in sperm parameters in dogs treated with Sodium chloride solution (Canpolat et al, 2016). The epididymal sperm concentration reflected a decrease in spermatogenesis in the testes (Oguejiofor et al, 2020). In the treatment groups, vacuolation of ductus epithelium of epididymis was detected.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have documented comparable results in terms of impaired spermatogenesis and reduced sperm parameters in dogs treated with sodium chloride solution [ 28 ]. According to Oguejiofor et al (2020) the observed decrease in epididymal sperm concentration can be attributed to a reduction in spermatogenesis in the testes [ 95 ].…”
Section: Discussionmentioning
confidence: 99%